Guide to inform relatives on sudden death in the emergency room - Falconi Chalco, Elizabeth (2013)
Emergency doctors are often obliged to report patient’s death to relatives. Professionals have not been prepared for this event but learn over time. In the present article, an unexpected death is that occurring in an individual chronically ill but controlled and compensated. Relatives do not expect his death and was not in their minds losing him. There are many national and foreign protocols on how to give bad news and how to communicate the death but none of them talk about this type of unexpected death. In this article, a 13 steps’ guide is proposed based both on experience obtained during 30 years of service in a hospital emergency and in specialized bibliography, guide adapted to our labor and cultural environment.